Rozwiązanie Pewnego Typu Tarczy Nieograniczonej - Wysiatycki, K. (Engineering Transactions, 1957)
A thin elastic cantilever slice is considered. The edges are straight lines and a circle. Using bipolar coordinates, the Airy function is found by separating variables and using the boundary conditions for a given function and its normal derivative at the edge. Solutions in closed forms are obtained for a few types of load often encountered in practice. For an arbitrary load, the solution is obtained by expanding theAiry function in a series of biharmonic polynomials. The stress distribution is illustrated by a numerical example.